1996
DOI: 10.1128/jb.178.13.3727-3735.1996
|View full text |Cite
|
Sign up to set email alerts
|

Growth phase-dependent transcription of the sigma(54)-dependent Po promoter controlling the Pseudomonas-derived (methyl)phenol dmp operon of pVI150

Abstract: Transcription from Pseudomonas-derived ؊24, ؊12 Po promoter of the pVI150-encoded dmp operon is mediated by the 54 -dependent DmpR activator in response to the presence of aromatic pathway substrates in the medium. However, global regulatory mechanisms are superimposed on this regulatory system so that the specific response to aromatic effectors is absent in cultures until the stationary phase is reached. Here we genetically dissect the system to show that the growth phase response is faithfully mimicked by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 45 publications
(64 reference statements)
5
103
1
Order By: Relevance
“…Previous data had shown that, in LB or minimal media containing casamino acids (CAA) as the sole carbon and energy source, transcription from the Po promoter was delayed until the exponential to stationary phase transition, whereas in minimal media containing glucose or organic acids, the transcriptional response from Po was immediate (Sze et al, 1996). These results suggest that the presence of amino acids in the media may be responsible for the delayed response, causing silencing of DmpR-mediated transcription until they had been depleted.…”
Section: Media Composition Determines When Dmpr-mediated Regulation Imentioning
confidence: 99%
See 4 more Smart Citations
“…Previous data had shown that, in LB or minimal media containing casamino acids (CAA) as the sole carbon and energy source, transcription from the Po promoter was delayed until the exponential to stationary phase transition, whereas in minimal media containing glucose or organic acids, the transcriptional response from Po was immediate (Sze et al, 1996). These results suggest that the presence of amino acids in the media may be responsible for the delayed response, causing silencing of DmpR-mediated transcription until they had been depleted.…”
Section: Media Composition Determines When Dmpr-mediated Regulation Imentioning
confidence: 99%
“…However, we have previously eliminated this possibility using a null rpoS mutant E. coli strain (Sze et al, 1996). Another obvious indirect mechanism by which the (p)ppGpp signal could act would be at the level of expression of known positive players in the DmpR-Po regulatory circuit.…”
Section: Modulation Of Po Activity By (P)ppgpp Is Not Caused By Indirmentioning
confidence: 99%
See 3 more Smart Citations